ANALISIS POTENSI BAHAYA KECELAKAAN MENGGUNAKAN METODE HIRA (HAZARD INDENTIFICATION AND RISK ASSESSMENT) PADA JALAN GATOT SUBROTO – JALAN RAYA SERANG - Siska Dewi; Raka Surya Pradana; Taqi Arya Suta; Ryandi Saputra; Bella Saskia Rahma Ayu (Universitas Tangerang Raya, 2025)
Road safety is a fundamental element of a safe, efficient, and sustainable transportation system. The high rate of traffic accidents in Indonesia, particularly those caused by physical road conditions and inadequate safety facilities, highlights the need for a proactive and data-driven prevention approach. This study aims to identify potential hazards, analyze accident risk levels, and formulate risk control recommendations on the Gatot Subroto – Serang Raya Road segment using the Hazard Identification and Risk Assessment (HIRA) method. The research was conducted through field surveys, collection of primary and secondary data, identification of road deficiencies, and risk assessment based on the likelihood and severity of impacts. The results show that moderate risk dominates at 56.7%, followed by high risk at 33.3% and low risk at 10%, with no extreme risk identified. The main hazards include pavement damage such as potholes, cracks, and uneven patches, differences in road surface elevation, and malfunctioning safety facilities such as traffic lights. These findings indicate that existing road conditions still pose significant safety risks if not promptly addressed. In conclusion, the application of the HIRA method is effective in systematically mapping risk levels and providing a decision-making basis for relevant authorities to improve road safety in a sustainable manner.